Influence of Digital Images on the Propagation of Fake News on Twitter in Russia and Ukraine Crisis - Aondover, Eric Msughter; Yar’Adua, Suleiman M.; Aondover, Perpetua Ogechi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2025)
Fake news, misinformation, and disinformation are problems in every country, especially during conflict. The Russian and Ukraine crisis witnessed an increased scope and impact of such fake images shared on Twitter to instigate the violence. Within this context, the study examines the influence of digital images on the propagation of fake news on Twitter in the Russia and Ukraine crisis. The objectives of the study are to (i) find out if fake digital images on Twitter are used as an attack tool (ii) to study digital images on Twitter as a platform for sharing fake news (iii) to investigate if digital images are used on Twitter as a pull prank, and (iv) to ascertain whether digital images on Twitter are used to derail the crisis. The theoretical lens of Technological Determinism and Visual Rhetoric Theories was used to serve the study goal. The study used Semiotic, and Qualitative Content Analysis as research methods. The population of the study consists of 10 fake images that were shared on Twitter with the period of the study. Purposive sampling was used to select eight images for analysis. The study discovered that fake digital images on Twitter were used as an attack tool. The findings of the study revealed that digital images on Twitter serve as a platform for sharing fake news. The study found that digital images are used on Twitter as a pull prank. Similarly, the findings of the study revealed that digital images on Twitter are used to derail the crisis. Based on the findings, the study concludes that the use of social media in spreading fake digital images in times of war like this should not be relied on as it will create more damage to such a crisis.